Exploring the top 30 drugs associated with drug-induced constipation based on the FDA adverse event reporting system - Li, Wenwen; Liu, Cuncheng; Zhang, Zhongyi; Cai, Zhikai; Lv, Tailong; Zhang, Ruiyuan; Zuo, Yaoyao; Chen, Shouqiang (Frontiers in Pharmacology, 2024)
Objective: This project aims to identify the top 30 drugs most commonly associated with constipation and their signal values within the FDA Adverse Event Reporting System (FAERS) database.We extracted adverse drug events (ADEs) related to constipation from the FAERS database spanning from January 1, 2004, to September 30, 2023. We compiled the 30 most frequently reported drugs based on the frequency of constipation events. We employed signal detection methodologies to ascertain whether these drugs elicited significant signals, including reporting odds ratio, proportional reporting ratio, multi-item gamma Poisson shrinker, and information component given by the Bayesian confidence propagation neural network. Furthermore, we conducted a time-to-onset (TTO) analysis for drugs generating significant signals using the medians, quartiles, and the Weibull shape parameter test.We extracted a total of 50,659,288 ADEs, among which 169,897 (0.34%) were related to constipation. We selected and ranked the top 30 drugs. The drug with the highest ranking was lenalidomide (7,730 cases, 4.55%), with the most prevalent drug class being antineoplastic and immunomodulating agents. Signal detection was performed for the 30 drugs, with constipation risk signals identified for 26 of them. Among the 26 drugs, 22 exhibited constipation signals consistent with those listed on the FDA-approved drug labels. However, four drugs (orlistat, nintedanib, palbociclib, and dimethyl fumarate) presented an unexpected risk of constipation.Ranked by signal values, sevelamer carbonate emerged as the drug with the strongest risk signal